A Novel Application of a Fourier Integral Representation of Bound States in Quantum Mechanics - Palma-Aguirre, G; Raff-Biggemann, U (2011)
A method is developed to find the bound state eigenvalues and eigenfunctions of one-dimensional and rotational symmetric three-dimensional quantum mechanical problems. The method is based on the fact that eigenfunctions of bound states are square integrable. We use this property and a judicious ansatz inspired on its asymptotic behavior to obtain a differential equation that can be solved straightforwardly using a Fourier transform. The main advantage of the method is that it avoids the traditional and tedious convergence analysis using a series representation. The method leads to an integral representation of the wave function and provides insight into concepts such as energy quantization, spectrum degeneracy, and bound states. © 2011 American Association of Physics Teachers.